2020
DOI: 10.3390/agronomy10121957
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Water in Agriculture in Mexico and Its Sustainable Management: A Bibliometric Review

Abstract: The development of agricultural activity in Mexico is generating environmental externalities that could compromise its future. One of the principal challenges facing the Mexican agricultural sector is to find a way to continue growing without jeopardising the availability and quality of its water resources. The objective of this article is to analyse the dynamics of the research on the use of water in agriculture in Mexico and its sustainable management. To do this, a review and a bibliometric analysis have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 68 publications
(76 reference statements)
0
11
0
6
Order By: Relevance
“…The violet cluster combines two priority themes: water resource management and land use and its changes. Given that a large part of Mexican agriculture is developed in arid and semi-arid climates where the availability of water resources is the principal limiting factor, the sustainable management of this resource is an urgent need [38]. Mexican agriculture has advanced greatly in terms of adopting technology to improve efficiency in water use.…”
Section: Abstract Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The violet cluster combines two priority themes: water resource management and land use and its changes. Given that a large part of Mexican agriculture is developed in arid and semi-arid climates where the availability of water resources is the principal limiting factor, the sustainable management of this resource is an urgent need [38]. Mexican agriculture has advanced greatly in terms of adopting technology to improve efficiency in water use.…”
Section: Abstract Analysismentioning
confidence: 99%
“…López-Hernández et al [81] analysed the productivityevapotranspiration relationship, concluding that the determination of productivity through evapotranspiration has a direct relationship with crop yields, as it improves irrigation efficiency. The modifications experienced in land use have been related to the different environmental impacts but particularly the degradation of water masses [38]. Vanderplank et al [82] reported that seawater intrusion into aquifers as a result of unsustainable extraction, mainly for agricultural irrigation, causes impacts on adjacent ecosystems, resulting in the loss of more than twenty native plants in the San Quintín valley.…”
Section: Abstract Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…industria y el agua potable. Esto sin duda indica que el agua, independientemente del uso que se le dé, tendría que ser gestionada de manera estratégica y sostenible (Gabriel, 2017;Ochoa-Noriega et al, 2020).…”
Section: Características Socioeconómicas Y Demográficas De Los Municipios Deunclassified